Modeling anticommons. The case of fisheries - Filipe, J. A. (2015)
Anti-Commons Theory explains new Property Rights concerns. An “anti-commons” problem arises when there are multiple rights to exclude. Little attention has been given to the setting where more than one person is assigned with exclusion rights, which may be exercised. “Anti-commons” problem is analyzed in situations in which resources are inefficiently under-utilized rather than over-utilized as in the familiar commons setting. In fact, these two problems are symmetrical in several aspects. Fisheries problems are studied.